R&D investment, financing constraints and corporate financial performance: Empirical evidence from China - Wang, Xiaohong; Fan, Min; Fan, Yaojun; Li, Yue; Tang, Xianghua (Frontiers in Environmental Science, 2022)
Enterprises are a deeply significant pillar of social and economic development. The excellent economic interests of enterprises play an essential role in promoting social and economic development. Business is a major innovation force in improving a country’s independent innovation capacity, which in turn is a key factor in shaping its core competitiveness. As the fuel of technological innovation for enterprises, Research and development (R&D) can accelerate their development and enhance their competitiveness. By using Chinese A-share listed companies from 2007 to 2019 as a sample, this study attempts to examine the specific impact of R&D investment by Chinese companies on corporate performance. Key to the development of R&D activities, R&D investment is directly related to the source of funding, the quality of financing channels and the extent of financing restrictions. The current study explains why enterprise innovation cannot be separated from the input and support of capital, technology, professional talent and other factors from the perspective of enterprise financing constraints. By using Chinese A-share listed companies from 2007 to 2019 as a sample, the study not only examined the impact of R&D investment on corporate performance, but also considered specific mediating mechanisms and heterogeneity analysis of R&D investment on corporate performance. Finally, the study found a significant positive correlation between R&D investment and the performance of listed companies, and this positive correlation was more pronounced when funding constraints were lower. According to the study, mediation effect analysis shows that R&D investment can improve corporate performance by boosting total factor productivity. Additional research has also shown that higher levels of internal control quality can improve the boosting effect of R&D investment on corporate performance. Moreover, R&D investment by SOEs is more conducive to improving the performance of their enterprises than that of non-SOE enterprises. In addition, this study provides empirical evidence of the knowledge effect and positive externality of R&D investment for firms, examines the impact of R&D investment on corporate performance from the perspective of financing constraints, and enriches the related literature on R&D investment, financing constraints and corporate performance.